Hepatoprotective Effect of Pisonia alba and Cardiospermum halicacabum in Atrazine Toxicity on LPO and some Antioxidant Activities in the Liver Tissue of Fresh Water Fish Labeo rohita - Pugazhendy, K (International Journal of Pharmaceutical & Biological Archive, 2014)
Hepatoprotective Effect of Pisonia alba and Cardiospermum halicacabum in Atrazine Toxicity on LPO and some Antioxidant Activities in the Liver Tissue of Fresh Water Fish Labeo rohita